(untitled) (Proceedings of the YSU C: Geological and Geographical Sciences, 2012)
Conducted short-time groundwater monitoring in the central part of Yerevan, especially in the section between stations named "Yeritasardakan" and "Zoravar Andranik" indicated that groundwater table is shallow and interferes with metro. For a rational reconstruction of the metro first the water table level should be lowered. To maintain the level of groundwater at relatively low depths it is required to develop and implement the necessary engineering measures.